Immunotherapy for opportunistic infections: Current status and future perspectives. Issue 8 (16th November 2016) - Fuji, Shigeo; Löffler, Jürgen; Einsele, Hermann; Kapp, Markus
ABSTRACT: The outcome after allogeneic haematopoietic stem cell transplantation (allo-HSCT) has significantly improved during the last decades. However, opportunistic infections such as viral and mold infections are still a major obstacle for cure. Within this field, adoptive T cell therapy against pathogens is a promising treatment approach. Recently, the techniques to develop T cell products including pathogen-specific T cells have been sophisticated and are now available in accordance to good manufacturing practice (GMP). Here, we aim to summarize current knowledge about adoptive T cell therapy against viral and mold infections.